EKSPLORASI ETNOMATEMATIKA PADA CANDI SIPAMUTUNG DESA SIPARAU - Siregar, Hanif Luthfi; Amanda, Anestasya; Alparwis, Ahmad Rifki; Mailani, Elvi; Kharismayanda, Mardhiyah (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
The aim of this research is to reveal and explain the mathematical concepts contained in the architecture of Sipamuthun Temple in Sipalau village. As a research field concerned with the relationship between culture and mathematics, ethnomathematics aims to gain a deeper understanding of the mathematical knowledge of past societies. The research method used is a qualitative approach using descriptive methods such as direct observation, documentation and library observation. The research results show that the design of Sipamuthun Temple displays a varied floor plan that reflects the complexity of the local community's mathematical knowledge. It is hoped that this research can increase public awareness of the importance of understanding mathematical concepts that exist in local culture and preserving existing cultural heritage.